Preclinical assessment of ulixertinib, a novel ERK1/2 inhibitor - Vinod Anera Balakrishna; Anitha Police; Rakesh Hiremath; Anusha Raj; Suresh P Sulochana; Devaraj V Chandrasekhar; Zainuddin Mohd; Ravi Kanth Bhamidipati; Ramesh Mullangi (International Association of Physical Chemists (IAPC), 2017)
Ulixertinib (BVD-523) is a novel and selective reversible inhibitor of ERK1/ERK2. In xenograft studies it inhibited tumor growth in BRAF-mutant melanoma and colorectal xenografts as well as KRAS-mutant colorectal and pancreatic models. Ulixertinib is currently in Phase I clinical development for the treatment of advance solid tumors. The objective of the study is to assess the metabolic stability (in various pre-clinical and human liver microsomes/hepatocytes), permeability, protein binding, CYP inhibition, CYP induction and CYP phenotyping of ulixertinib. We have also studied the oral and intravenous pharmacokinetics of ulixertinib in mice, rats and dogs. Ulixertinib was found to be moderately to highly stable in various liver microsomes/hepatocytes tested. It is a medium permeable (2.67 x 10-6 cm /sec) drug and a substrate for efflux (efflux ratio: 3.02) in Caco-2 model. Ulixertinib was highly bound to plasma proteins. CYPs involved in its limited metabolism and it is CYP inhibition IC50 ranged between 10-20 µM. Post oral administration ulixertinib exhibited early Tmax (0.50-0.75 h) in mice and rats indicating absorption was rapid, however in dogs Tmax attained at 2 h. The half-life (t½) of ulixertinib by intravenous and oral routes ranged between 1.0-2.5 h across the species. Clearance and volume of distribution by intravenous route for ulixertinib were found to be 6.24 mL/min/kg and 0.56 L/kg; 1.67 mL/min/kg and 0.36 L/kg and 15.5 mL/min/kg and 1.61 L/kg in mice, rats and dogs, respectively. Absolute oral bioavailability in mice and rats was > 92 %, however in dogs it was 34 %.